2009
DOI: 10.4049/jimmunol.0900034
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory and Inhibitory Killer Ig-Like Receptor Molecules Are Expressed and Functional on Lupus T Cells

Abstract: T cells from lupus patients have hypomethylated DNA and overexpress genes normally suppressed by DNA methylation that contribute to disease pathogenesis. We found that stimulatory and inhibitory killer cell Ig-like receptor (KIR) genes are aberrantly overexpressed on experimentally demethylated T cells. We therefore asked if lupus T cells also overexpress KIR, and if the proteins are functional. T cells from lupus patients were found to overexpress KIR genes, and expression was proportional to disease activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 37 publications
3
63
0
Order By: Relevance
“…T cells normally express very few or no KIRs, although KIR expression can be detected on a small subset of T cells in patients with autoimmune diseases, such as lupus and rheumatoid arthritis (22,(26)(27)(28)(29)(30)(31). It is suspected that KIR expression on the subset of T cells in these conditions may play a role in regulating aberrant T-cell responses that are associated with the initiation and/or progression of the diseases (13,15,22,29,30). Beyond this, little is known about the role of KIRs in T cells, and expression of KIRs in Tregs has not been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells normally express very few or no KIRs, although KIR expression can be detected on a small subset of T cells in patients with autoimmune diseases, such as lupus and rheumatoid arthritis (22,(26)(27)(28)(29)(30)(31). It is suspected that KIR expression on the subset of T cells in these conditions may play a role in regulating aberrant T-cell responses that are associated with the initiation and/or progression of the diseases (13,15,22,29,30). Beyond this, little is known about the role of KIRs in T cells, and expression of KIRs in Tregs has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, activating KIRs are implicated in conditions including active host defense against infectious organisms (23)(24)(25). Normal T cells express very few or no KIRs, but KIR expression can be detected on a small subset of T cells in patients with autoimmune diseases, such as lupus and rheumatoid arthritis (22,(26)(27)(28)(29)(30)(31). Based on these studies, it has been proposed that KIR expression may play a role in aberrant T-cell responses (13,15,22,29,30).…”
Section: Both Foxp3mentioning
confidence: 99%
“…1 For example, CD8 T cells from patients with systemic lupus erythematosus expressed higher frequencies of KIR than those from healthy individuals. 42 Furthermore, celiac disease has been associated with the appearance of KIR ϩ intraepithelial CD8 T cells in the gut lumen, 43 and rheumatoid arthritis caused an accumulation of KIR ϩ CD28 Ϫ CD4 T cells. 21,23 Because most available antibodies against KIRs display cross-reactivity and recognize both activating and inhibitory receptor forms, the role of activating KIRs in the context of these autoimmune conditions could not be examined in detail on primary cells in those published studies.…”
Section: Kir2ds4mentioning
confidence: 99%
“…KIR/ HLA ligand interactions were especially diverse. And a great number of previous studies have demonstrated associations between inheritance of certain combinations of KIR and HLA genes and susceptibility to many different diseases, including viral infections, autoimmune disorder, cancers, etc [43][44][45][46]. In general, HLA-C1 was the ligand of KIR2DL2/3 and KIR2DS2, and HLA-C2 was the ligand of KIR2DL1 and KIR2DS1.…”
Section: Discussionmentioning
confidence: 99%